Between adoption and rejection: attitudes of adult educators toward digitization in Germany. (12th January 2020) - Rohs, Matthias; Bolten, Ricarda; Kohl, Jonathan
Abstract : The use of digital media in adult education is very heterogeneous. To date, there are no empirical studies that have examined the possibility that media‐related differences in media usage of adult educators could be in part due to differential media pedagogical attitudes of adult educators. Moreover, there is a lack of empirical evidence to support the understanding of what factors modulate differences in media pedagogical competencies of adult educators. In order to examine different theoretical potentialities, in the present study, an online survey of adult educators ( n  = 626) was conducted to investigate the attitudes of adult educators in Germany toward their use of digital media. The results of the study indicate that there are influencing factors such as educational level or employment context on attitudes toward digital media.